A new approach to design asymptotically stabilizing control and adaptive control. (31st July 2018) - Noori Skandari, Mohammad Hadi; Nazemi, Alireza
Summary: In this paper, we propose a new approach to design the asymptotically stabilizing control and adaptive control for nonlinear systems. We first propose an infinite‐horizon optimal control (OC) problem according to the nonlinear control system. We prove that its OC can be an asymptotically stabilizing control or adaptive control for the original nonlinear system. Then, we convert the infinite‐horizon OC problem into an equivalent finite‐horizon OC problem. Moreover, we utilize the Legendre pseudospectral method to solve the proposed problem. Finally, several examples are given to illustrate the efficiency of the approach.